2005
DOI: 10.1111/j.1365-2567.2005.02207.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin‐derived dendritic cells acquire and degrade the scrapie agent following in vitro exposure

Abstract: Summary The accumulation of the scrapie agent in lymphoid tissues following inoculation via the skin is critical for efficient neuroinvasion, but how the agent is initially transported from the skin to the draining lymph node is not known. Langerhans cells (LCs) are specialized antigen‐presenting cells that continually sample their microenvironment within the epidermis and transport captured antigens to draining lymph nodes. We considered LCs probable candidates to acquire and transport the scrapie agent after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 52 publications
6
32
1
Order By: Relevance
“…Moreover, we found that LPS-activated BMDC or BMM showed an accelerated breakdown of PrP bse , suggesting that the process of capture and clearance of PrP bse can be increased following DC maturation or macrophage activation. Our results differ from those of Mohan et al, who showed an inhibition of PrP sc clearance when skin-derived DC were activated by LPS (28). This difference could be due to the prion strain or the subset of DC.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Moreover, we found that LPS-activated BMDC or BMM showed an accelerated breakdown of PrP bse , suggesting that the process of capture and clearance of PrP bse can be increased following DC maturation or macrophage activation. Our results differ from those of Mohan et al, who showed an inhibition of PrP sc clearance when skin-derived DC were activated by LPS (28). This difference could be due to the prion strain or the subset of DC.…”
Section: Discussioncontrasting
confidence: 57%
“…This difference could be due to the prion strain or the subset of DC. (28). We found that although PrP bse was not detected within the cell culture at 6 days following incubation with BSE prions, infectivity still exists, confirming that the bioassay presents a very superior sensitivity level of infectivity.…”
Section: Discussionsupporting
confidence: 55%
“…2 and 5 (14,(30)(31)(32)(33)(34), and PrP Sc in scrapie-infected cells can be degraded by cocultivation with dendritic cells (35,36). Our data demonstrate that cells disaggregate PrP Sc within the first 24 h following infection with scrapie.…”
Section: Smaller Prpmentioning
confidence: 60%
“…Impaired microglial migration in CXCR3 Ϫ/Ϫ mice may well contribute to decreased phagocytosis and consequently less degradation of PrP Sc deposits, because only migratory microglia can be expected to efficiently reach deposits of misfolded protein for subsequent engulfment. A role of phagocytes in uptake and degradation of PrP Sc has been demonstrated in cell cultures (10,11,45) and in prion-infected animals (2,42). Moreover, depletion of microglia from prion-infected organotypic brain slices was shown to promote dramatic increases in PK-resistant PrP Sc and prion infectivity (19).…”
Section: Discussionmentioning
confidence: 99%